KAJIAN IMPLEMENTASI PIRANTI THERMOELECTRIC (PELTIER) SEBAGAI SISTEM PENGATUR SUHU THERMOS PENYIMPAN SPERMATOZOA - Hariyadi Singgih; Subiyantoro Subiyantoro; Siswoko Siswoko (Politeknik Negeri Malang, 2018)
One alternative application of technology in the field of animal reproduction is by artificial insemination technology (IB). Artificial Insemination Process (IB) is a technique for inserting spermatozoa or semen which has been melted and processed first into the female genital tract. To obtain good quality cement, cow sperm preservation by dilution and followed by cooling to 5 ° C (chilling process). The chilling process with cement storage using 5 ° C will keep the cement life of 7 to 10 days. For this fulfillment, the Thermos box prototype is designed as a spermatozoa storage device to ensure good cement quality. The research method is design of prototype tool using Thermoelectric TEC (peltier) type device TEC1-12706T200. And use the LM35 temperature sensor device to detect the temperature in the box. Thermos. This study examines the efficiency of time required by the system when it reaches 5.0 ° C. and influential parameters in accelerating the temperature performance of 5.0 ° C. The readable temperature of the LM35 sensor will be displayed on a 16x2 LCD monitor. Data processing system using Arduino Microcontroller. Measurement result and performance assessment of Thermoelectric TEC (peltier) device type TEC1-12706T200 when it reaches maximum working temperature 5,5 º C within 8 hours. has an error of 2.5%. which depends on the size of the power supply (Current) electricity.